A mild one-pot process for synthesising hydroxyapatite/biomolecule bone scaffolds for sustained and controlled antibiotic release. (16th January 2015) - Hess, Ulrike; Hill, Sebastian; Treccani, Laura; Streckbein, Philipp; Heiss, Christian; Rezwan, Kurosch
Abstract: The release of active molecules or the control of nosocomial infections for improved osteoinduction is ideally addressed by a bone substitute material. For this purpose, the feasibility of a mild one-pot process is probed for incorporating directly active proteins and antibiotics in a hydroxyapatite (HAp) based scaffold. The effect of two serum model proteins, bovine serum albumin (BSA) and fibrinogen (FIB), on the microstructure, on selected mechanical properties as well as on degradation behaviour and on protein release are investigated. By protein incorporation, the porosity can be adjusted between 54 and 70% especially due to the foaming ability of BSA. The addition of 5 wt% FIB doubles the biaxial flexural strength up to 6 MPa in comparison to samples without proteins (3 MPa). Protein release experiments show that a rapid release takes place within the first days (between around 3% for FIB and 38% for BSA). As a possible application for osteomyelitis treatment, vancomycin and gentamicin were subsequently added instead of proteins to study their release behaviour and their antibacterial activity, respectively. A controlled antibiotic release was observed for a period of 18 d. By varying the protein type, mixture and quantity, the mechanical strength porosity as well as the protein release and calcium solubility can be controlled. Our studies underpin the suitability of this mild one-pot process as a promising simple-to-use platform for controlled local drug release and bone treatment.